An investigation of the key Challenges and Resolutions for Sustainable Groundwater Management in Paktika, Afghanistan - Hizbullah Rahmani; Mohammad Omar Abi; Noor Mohammad Azizi (Randwick International of Social Science Journal, 2022)
If Afghanistan's current environmental problems are not addressed, the consequences could include severe water scarcity in some areas, which could threaten livelihoods, create environmental refugees, exacerbate adverse humanitarian conditions, and increase regional tensions. Therefore, the study was conducted in Sharana, the center of Paktika province, and was attended by 45 farmers. The goal of the research was to determine the major threats to Sharana's groundwater resources. For this study, questionnaires and field observations were chosen as techniques. according to the study's findings that drought, increased use of solar-powered submersibles, a lack of water management plan, a lack of regulations related to groundwater exploitations, and extensive use of underground water for irrigation due to farmers' lack of awareness and traditional irrigation systems are among the key challenges threatening groundwater in Paktika. Because the groundwater level has dropped, it is not unlikely that this situation may turn into a disaster if it continues. The primary components that can contribute to the sustainability of groundwater resources management in Paktika city are raising public knowledge about water resources management, switching to smart irrigation techniques, and adopting an integrated water resources management framework.